Emberi bánásmód veszteségek idején - Alpár Csaba NAGY (Studia Universitatis Babeş-Bolyai. Theologia Reformata Transylvanica)
Humane Treatment of People Who Experience Losses. In this paper, we present the grief as a natural response to the losses that people experience. We regard grief as an adaptive mechanism to the new situa-tion that occurs with a loss. In our success-oriented consumerist society, grief has become a taboo: fighting pain in losses became a sign of weakness and fail-ure. This is valid also for Christians, who consider faith as the measure of suc-cessful dealing with distress. We present the positive perceptive structures that may help the grief – based on Anil Seth’s theories. Later on, we speak about the toxic positivism, which harms the grieving person and the adequate expression of condolence, which may express our participation in his/her tormented situation. Destructive attitude consists in shaming, abandoning, or betraying the grieving person, whereas constructive attitude means acceptance, condolence, and sup-port. This paper tries to provide a practical guideline to an empathic grief coun-selling.